(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to evaluate the growth, survival and production performances of pangus (Pangasianodon hypophthalmus) and shing (Heteropneustes fossilis) in which shing was used as guest to utilize the waste energy in pangus pond. The experiment was run for four months from July to October, 2008. Fishes were reared in pond no I, II, III with stocking density 150, 250 and 300 per decimal of pangus respectively. Shing was stocked only 10/decimal in pond-I. A complete artificial feed was used containing 23% protein. The weight gain (385.17±2.15g) of pangus was significantly higher in pond-I than that of pond-II (325.15±2.70g) and pond-III (319.30±2.90g). However, the production of pangus per ha were (28158.00±0.10kg) in pond-I, (34159.112±0.50 kg) in pond-II and (37856.208±0.60 kg) in pond-III. Total production of shing in pond-I was 240.57±1.60 kg/ha/yr. The survival rates (%) of pangus under three stocking densities were 98.66%, 85.06% and 80.00% respectively. The food conversion ratio (FCR) of pangasius pond I, II and III were 1.53, 1.81 and 1.84 respectively. The lowest FCR of 1.53 was found in pond-I. The net return of the pond I, II and III were BDT 273503.10, 117456.73 and 107906.60 per ha per year. The addition of shing into pangasius pond as guest invites economic benefit to the pangus culture. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22067 J. Environ. Sci. & Natural Resources, 6(1): 209-216 2013